ANALISIS PENGGUNAAN KONFIGURASI RUNWAY 03 DAN 31 DALAM KELANCARAN LALU LINTAS UDARA DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Lutfi Handika Pratama; Yuyun Suprapto; Chaeruddin (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In providing air traffic services, an Air Traffic Controller must prioritize the safety and smooth movement of traffic. The runway configuration applied at Sultan Hasanuddin Airport Makassar, there was a buildup of traffic departures causing a decrease in the level of smoothness in the aircraft movement area. In the use of runway 03 and 31 configurations, there is a meeting of arrival aircraft passing through the rapid exit taxiway with departure aircraft on the whiskey papa taxiway heading to runway 31. So that the movement of the aircraft becomes obstructed and unsafe for aircraft holding on the taxiway delta. The accumulation of traffic departures often occurs during peak hours, even though the time slot has been enacted. Slot time is the schedule of arrival and departure times allocated by the ATFM coordinator for aircraft movement at a set time/date that is adjusted/aligned with existing airport facilities. There needs to be equity by allocating time to a more tenuous schedule so that there is no buildup. Increased coordination with APP is needed to increase the separation between departure and arrival aircraft, and not instruct aircraft to hold on to the delta taxiway if there has been a buildup of departure traffic, which is expected to be able to reduce this problem. The results of the research that has been carried out by the author at the Sultan Hasanuddin International Airport in Makassar are expected to provide an alternative to solving problems that arise due to the influence of the runway configuration. The author also hopes that this research can be useful to improve flight safety and create a safe, comfortable, regular and efficient air traffic service at Sultan Hasanuddin International Airport Makassar.